Analysis of the Influence of Tile Surface Oil-taking on Bearing Capacity of Thrust Bearing - Yu Xiangdong; Liu Yuan; Li Yuefeng; Cheng Xiaoming (Jixie chuandong)
Based on FLUENT software，the CFD analysis model of tile surface oil-taking of thrust bearing is established. The influence of tile surface oil-taking groove pressure，position and width on the bearing capacity of thrust bearing is studied. Research shows that reasonable tile surface oil-taking groove design is beneficial to improve the bearing capacity of the thrust bearing. When the oil groove pressure reaches a certain value， it has a positive pressurization effect on the oil film. The oil groove should be close to the side of tile entering oil. The width of the oil groove has little effect on the bearing capacity. The heavy-duty thrust bearing device with tile surface oil-taking is developed，the performance test and 1 100 h long-distance running test are carried out，a reference for the design of the lubrication system for thrust bearing is provided.